Emotions as Subject of Lithuanian Folksong Research - Sadauskienė, Jurga (Tautosakos darbai, 2014)
The article presents a survey of Lithuanian folksong research from the earliest until the most recent studies. Special emphasis is placed on evaluation of the emotional character of the songs in the works by the folklore collectors and researchers. The author attempts to establish causes of the special attention devoted to emotionality in the folksong research. The presented examples show that: 1) in the studies written during the 18th–19th centuries, emotions were used as an argument to prove the capacity of small nations and lower social classes to create artistically valuable texts, thus becoming equal to the more economically advanced peoples and aristocracy; 2) in the end of the 19th – beginning of the 20th century, peculiarities of the songs’ emotionality were emphasized as expressions of the national character and uniqueness formed by the particular landscape, the nation’s historical destiny and its way of life; 3) in the middle of the 20th century, scientists tended to devote increasing attention to emotionality of the text as constituent of its esthetical value (e. g. studies by Donatas Sauka and Leonardas Sauka particularly reveal ways that poetic means are used by the folksongs to achieve ultimate suggestive effect, thus proving that lyricism is predominant and exceptional poetic feature of the Lithuanian folksongs); 4) in the end of the 20th–beginning of the 21st century attention is increasingly shifted towards psychology of the singing, the singer’s feelings and his / her artistic self-expression as a kind of therapy. New arguments to actualize study of emotions in the folklore research are sought at present.
Keywords: -